The diverse Types of Language in Miftāḥ al-sa‘āda of Ibn al-‘Arīf (m. 536/1141) - Shafik, Ahmed (’Ilu. Revista de Ciencias de las Religiones, 2012)
Study that try to expose and to define the different types of the language as the juridical, theological, and ascetic-mystical in Miftāḥ al-sa‘āda [Key of Happiness] of Ibn al-‘Arīf. Types that are analyzed in details, to conclude with the influence of the Sufi language of Ibn al-‘Arīf in Ibn ‘Arabī’s work, supporting on considerations of semantic as well as mystical nature.